The Effect Of Instagram Social Media Use On The Self-Healed Ability Of Students Of The University Of North Sumatera - All rizky ramadhan siregar; Andre Genesa Harahap; Anugerah Zebua; Natalia Syafitri Br Marpaung (Journal Analytica Islamica, 2024)
This research is entitled "the effect of the use of social media Instagram on the self healing ability of Universitas Sumatera Utara students". The purpose of the study was to knowing the use of Instagram social media among USU students and knowing the effect of using Instagram social media on the self healing abilities of USU students. The theory used is Communication Psychology, Intrapersonal Communication, Self Healing Method, Self Commpassion, Emotional Control, New Media, Social Media, Instagram, Uses and Gratification. The research method is correlational quantitative. This research applies accidental sampling technique. The data collection technique used is through a questionnaire. The researcher conducted a series of data analysis techniques, single table analysis, cross table analysis, and Spearman's tiering coefficient hypothesis test. The results showed that there was a significant effect on the use Instagram social media on the self-healing ability of Universitas Sumatera Utara.. Hypothesis testing shows that there is a significant relationship between the two variables. Through the correlation determinant test, it was found that Instagram usage had on the self healing ability of students Universitas Sumatera Utara.